Efek Nefrotoksik Ekstrak Etanol Akar Putri Malu (Mimosa pudica L.) pada Ginjal Mencit (Mus musculus) - La Eddy; Joseph Pagaya; Emma M de Fretes; Abdul M Ukratalo (PPNI UNIMMAN, 2025)
Mimosine is an aromatic amino acid found in Mimosa pudica L. (sensitive plant) and is known to possess toxic properties that can damage various organs, including the kidneys. This study aimed to investigate the effect of ethanolic root extract of Mimosa pudica on renal damage in mice (Mus musculus). Twelve mice were divided into four groups: a control group and three treatment groups that received ethanolic root extract of M. pudica at doses of 10 mg/mouse/14 days, 100 mg/mouse/14 days, and 1000 mg/mouse/14 days. Following treatment, the mice were dissected to measure serum creatinine levels as an indicator of renal function, and histopathological observations of kidney tissues were performed using Hematoxylin-Eosin staining. The results revealed that administration of the ethanolic root extract of M. pudica significantly increased serum creatinine levels (P < 0.05), indicating impaired renal filtration function. Histologically, several types of tissue damage were observed, including glomerular atrophy, hydropic degeneration, and cellular necrosis, with hydropic degeneration being the most predominant and glomerular atrophy the least frequent. These findings suggest that mimosine, an active compound in M. pudica roots, exhibits a dose-dependent nephrotoxic effect, where increasing extract concentrations exacerbate renal tissue damage. Therefore, caution is advised in the medicinal use of M. pudica, as despite its pharmacological potential, high-dose or prolonged exposure may pose a serious risk of renal dysfunction.